ANALYSIS OF EMI GENERATED BY ELECTRONIC SUPPLY SOURCES CAUSING DISFUNCTIONS IN SIGNAL PROCESSING SYSTEMS, MOBILE COMMUNICATIONS INCLUDED - M. E. Bagheryan-Marzooni; G. V. Berberyan (ՀՀ ԳԱԱ հրատ.)
EMI generation and propagation mechanism, high rates of of voltage and current change in fast switching power devices (such as using IGBT), modeling and identifying EMI (noise) sources and their coupling paths with the signal processing circuitry have been discussed. A practical EMI measurement system has been suggested to extract more information from noise through analysis in frequency and time-domains and test EMI emitting equipment to comply with electromagnetic compatibility (EMC) standards. Different filter topologies have been analiz0 ed for decreasing the EMI originated by negative effect exertion of high dv/dt and di/dt due to high frequency switching.
Keywords: Electrical engineering; Electronics; Nuclear engineering; Technology